2022
DOI: 10.1021/acscatal.2c00265
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Enhanced Oxygen Evolution Reaction in Flexible van der Waals LaNiO3 Membrane

Abstract: The atomic-level catalysis mechanism of various electrochemical processes can be achieved via the perovskite transition metal oxide (TMO) thin film with accurate stoichiometry and lattice ordering, which boosts the design and engineering of further promising catalysts. In the oxygen evolution reaction (OER), owing to the correlation nature of the TMO, strain can effectively tune the OER performance by modulating the electron occupancy and strengthening the exchange/coupling. However, the surface strain conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Consequently, the electrocatalytic performance is significantly enhanced. 151,152 For tensile strain, the increase in the interatomic distances of the late transition metals and early transition metals at the heterointerface can cause the d-band center to shift up and down, respectively. 153 Importantly, the upward shift of the d-band center increases the antibonding state energy in the catalyst-adsorbate system (Figure 13A) and reduces the antibonding state filling, which in turn enhances the interaction between the catalyst and the reactants (or reaction intermediates).…”
Section: Lattice Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the electrocatalytic performance is significantly enhanced. 151,152 For tensile strain, the increase in the interatomic distances of the late transition metals and early transition metals at the heterointerface can cause the d-band center to shift up and down, respectively. 153 Importantly, the upward shift of the d-band center increases the antibonding state energy in the catalyst-adsorbate system (Figure 13A) and reduces the antibonding state filling, which in turn enhances the interaction between the catalyst and the reactants (or reaction intermediates).…”
Section: Lattice Strainmentioning
confidence: 99%
“…These strains modulate the d‐bandwidth of the material by affecting the overlap degree of the wave function, optimizing the adsorption capacity of the catalytic site for reaction intermediates. Consequently, the electrocatalytic performance is significantly enhanced 151,152 . For tensile strain, the increase in the interatomic distances of the late transition metals and early transition metals at the heterointerface can cause the d‐band center to shift up and down, respectively 153 .…”
Section: Impact Of Interface Engineering On Electrocatalysismentioning
confidence: 99%
“…The new tools described in this review to produce freestanding complex-oxide membranes would enable: (a) Increasing the surface-to-volume ratio by (e.g. by using rolled-up nanomembrane tubes [56,95], (b) Accessing extreme-strain states where theory predicts increasing favorability of surface oxygen dissociation [256] but are not accessible in epitaxial heterostructures, (c) Actively tuning the catalytic activity via mechanical actuation [257], (d) Using mechanical detection methods to identify strains associated with catalytic processes [258], (e) Fabricating electrocatalytic cells to characterize the atomic and electronic structure of metal-oxide compounds interfaced with gases and liquids, using ambient pressure conditions (figure 8(c)) [259,260].…”
Section: Electrochemistrymentioning
confidence: 99%
“…[28,29] Lanthanum cobaltate (LaCoO 3 , LCO) is a typical and representative perovskite cobalt oxide with the general formulation of ABO 3 , which has received the most attention in electrocatalytic OER due to its simple preparation process, distinctive electrical, structural, magnetic and catalytic characteristics. [30][31][32][33] However, the electrocatalytic activity of LCO is severely restricted, which is the result of the dissatisfactory adsorption of oxygen-containing intermediate due to inappropriate spin configuration of Co ions. [34] Previous work demonstrated that more than one A-site and/or B-site cation can be admitted into the perovskite structure since it possessed the admirable tolerance of lattice heterogeneity and mismatch between different metal (A/B)À O bond lengths.…”
Section: Introductionmentioning
confidence: 99%